Islamic architecture - context: Kuala Lumpur / Siti Azurah Mohamed Ghazali. - Mohamed Ghazali, Siti Azurah (1987)
Its definition is usually based on the building itself, the concept of planning and spaces, inter-relationship between the spaces, the material and decoration applied onto the particular building. With this understanding, it is supposed to mirror harmony, unity and the belief that there is Allah. It is also then further harmonized with colours, which are bright and emphasizes the importance of Islam. During the rule of the Ummayad, the arts of decorations were at its peak of magnificence and creativity. These Arabs and also others were exposed to the beauty of nature and its surroundings.